2012
DOI: 10.1097/01.asw.0000423439.62789.90
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Topical Oxygen for the Treatment of Chronic Wounds

Abstract: Oxygen is essential for all stages of wound healing. Previous research has shown topical administration of oxygen to have positive effects on wound healing. In this study, the application of transdermal continuous topical oxygen therapy (TCOT) was evaluated for its effect on chronic wound healing in 9 patients. After 4 weeks of treatment, mean wound surface area and wound infection checklist scores were significantly reduced. Signs of bacterial damage were also reduced. Findings from this study suggest TCOT ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…71 The lack of a formal study in this regard has been offset by several reviews, case series, and experimental studies on the effect of topically administered oxygen at the wound surface that seem to indicate a benefit in promoting wound repair. 154,[159][160][161][162][163][164][165][166][167][168][169] While several RCTs with different devices have been ongoing, there have been no publications to date comparing 12-week healing rates with those of standard care.…”
Section: Negative Pressure Wound Therapymentioning
confidence: 99%
“…71 The lack of a formal study in this regard has been offset by several reviews, case series, and experimental studies on the effect of topically administered oxygen at the wound surface that seem to indicate a benefit in promoting wound repair. 154,[159][160][161][162][163][164][165][166][167][168][169] While several RCTs with different devices have been ongoing, there have been no publications to date comparing 12-week healing rates with those of standard care.…”
Section: Negative Pressure Wound Therapymentioning
confidence: 99%
“…Malodour was used in 25 studies with a total of 1298 CLUs and erythema was used in 25 studies with 811 CLUs 12,14,22,34,37,38,41,45,47,50,51,[53][54][55][56][57][58][59][60][61][62][63][64][65][66] (Table 4). Malodour has been used in combination with other clinical signs 41,58,62 and/or microbial indicators. 45,[67][68][69] However, in a study that investigated the roles of specific bacteria in wound malodour production between 43 infected and 30 non-infected leg ulcers, the authors found malodour presented in both infected (18.6%) and non-infected leg ulcers (6.7%), (level III),.…”
Section: How Have Clinical Signs and Symptoms Of Infection Been Usementioning
confidence: 99%
“…Oedema was used in 22 studies with a total of 484 CLUs. 12,14,22,37,38,41,47,48,50,[54][55][56][57][58][59][60]62,73 Seventeen studies used increased temperature around the wound or warmth or hot to touch to diagnose infection in nearly 250 CLUs. Seventeen reviewed studies used delayed healing to diagnose infection in 181 CLUs, five studies used increased ulcer area in almost 500 CLUs, and wound breakdown was also used in five studies with almost 200 CLUs.…”
Section: How Have Clinical Signs and Symptoms Of Infection Been Usementioning
confidence: 99%
“…12 These results have been validated in small cohorts of chronic wound patients, where the wounds experienced some healing during treatment. 14–16 …”
Section: Introductionmentioning
confidence: 99%